IR SPECTROSCOPIC ANALYSIS OF BIAXIALLY DIRECTED POLYPROPYLENE AND POLYETHYLENE POLYMER FILMS - ESHBAEVA, ULBOSIN; SAFAEVA, DILAFRUZ; ZUFAROVA, DILOBAR; BALTABAEVA, BARNO (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
In this article, calculation of IR spectra of experimental polymer materials after corona discharge, chain length, intensity of IR spectroscopic absorption fields of oriented polymers, polarization and effect of chain length on normal frequencies were researched. A significant increase in surface energy is observed when treating the surface of biaxially oriented polypropylene and polyethylene polymer films with a corona charge. As a result of the chemical interaction of the polymer material with the solution, active groups are formed in the surface layer, which react with the surrounding nitrogen, hydrogen, argon and oxygen.